Smart ageing with sway: Opportunities and challenges - Zhaohui Su, Ph.D.; Ruijie Zhang; Dean McDonnell, Ph.D.; Barry L Bentley, Ph.D.; Yayra Kweku Adobor; Jianlin Jiang; Yifan Liu; Xin Yu; Ruru Chen, Ph.D.; Tumaresi Alimu, Ph.D.; Xinxin Wu, Ph.D.; Ali Cheshmehzangi, Ph.D.; et al. (Archives of Gerontology and Geriatrics Plus, 2024)
Smart ageing is the process of leveraging accessible socio-ecological opportunities to proactively build the desired lifestyle and preferred quality of life as people age. Different from other ageing models, smart ageing views the ageing process from a socio-ecological perspective, a process which is shaped by the interplay of social, cultural, economic, political, and technological factors, along with medical ones. Rather than taking a one-size-fits-all approach and pre-emptively defining a “universal” factor that decides the ageing process, smart ageing respects and emphasises individuals’ agency and efficacy in deciding what is important and appropriate to their well-being and designing their own ageing journey. While smart ageing can be a solution to population ageing, ingrained inequality issues like the digital divide can nevertheless hinder its ability to help people age at their own pace and with grace. To shed light on the issue, this paper examines the tsunami of social issues population ageing could unleash, and discusses how the smart ageing model—along with its opportunities and challenges—can help people better navigate their ageing adventure.